PENTINGNYA PERAN MANAJEMEN HUBUNGAN MASYARAKAT DI LEMBAGA PENDIDIKAN - Nur Azizah, Muslihatul; ‘Ilmiya, Nasyith; Haibah, Risti Nisrina; Zakiyatun Nuha, Zahwa; Sulistyorini (Program Studi Manajemen Pendidikan Islam, 2024)
This research aims to examine in depth the importance of public relations management in educational institutions in building a positive image of educational institutions. Through literature studies, this research analyzes various literature related to the objectives and functions of public relations management, the role of public relations in educational institutions and building a positive image in educational institutions. The results of the study show that public relations management has a crucial role in shaping public perceptions of educational institutions. Public relations management acts as a communication bridge between educational institutions and various internal and external publics, including students, teachers, parents, the community and the government. Effective communication can increase involvement of all parties, strengthen relationships, and achieve common goals. Effective communication strategies, managing relationships with various internal and external publics, as well as quick responses to public issues are the keys to building a positive image and good reputation for educational institutions.